2009
DOI: 10.1212/wnl.0b013e3181b7849b
|View full text |Cite
|
Sign up to set email alerts
|

Leisure activities and the risk of dementia in the elderly

Abstract: Our findings support the hypothesis that cognitively stimulating leisure activities may delay the onset of dementia in community-dwelling elders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
217
2
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(240 citation statements)
references
References 38 publications
12
217
2
9
Order By: Relevance
“…As for socio-demographic factors, corroborating other studies 6,20,32,40,47,48,49 , we found that more schooling significantly reduced the odds of cognitive decline.…”
Section: Discussionsupporting
confidence: 91%
“…As for socio-demographic factors, corroborating other studies 6,20,32,40,47,48,49 , we found that more schooling significantly reduced the odds of cognitive decline.…”
Section: Discussionsupporting
confidence: 91%
“…In an attempt to more clearly understand the health promoting mechanisms of leisure occupations, a number of international studies have explored the relationship between occupational engagement over time and ageing well (Akbaraly et al, 2009;Chen & Fu, 2008;Dodge et al, 2008;Droogleever Fortuijn et al, 2006;Haggblom-Kronlof & Sonn, 2005;Menec, 2003;Nilsson, Lofgren, Fisher, & Bernspang, 2006;Paillard-Borg et al, 2009;Simone & Haas, 2009;Strain, Grabusic, Searle, & Dunn, 2002). In the Aging in Manitoba study, Menec (2003) used a 21-item leisure activity checklist to examine the relationship between overall participation levels, as well as doing particular occupations, and everyday function, wellbeing and mortality.…”
Section: Everyday Occupations and Ageing Wellmentioning
confidence: 99%
“…Já no grupo 3 esse risco foi de 32,4% (Tabela 2). no declínio cognitivo em idosos, exercendo influência no risco de demência 24,17 . Alguns autores evidenciaram que altos níveis de atividades físicas, mentais e sociais associam-se igualmente a um risco de demência reduzido e que a prática simultânea de dois ou dos três componentes exercem efeitos ainda mais pronunciados na redução do risco 16 .…”
Section: Resultsunclassified